The use of antidepressants for the treatment of a variety of diseases except depression in Homs governorate and study the relation of its disbursement with: Genus, age, sex - Al Salem, Nour (Journal of medical and pharmaceutical sciences, 2017)
This research aims to estimate the ratio of anti-depressants issued within the governorate of Homs, as well as identifying the relationship between the demand for anti-depressants and each of the following variables: Type – Age – Sex. Methods: A statistical study has been conducted by issuing forms and surveys to a random sample of participants. The number of medical cases included in the study is 350 cases divided between both genders, and different age groups within Homs governorate. Results: The study shows that the demand for anti-depressants of the type (TCAs) reached 71.42% amongst the study sample, followed by (SSRIs) which capped at 24.85%. The data also indicates that 76,00% of prescribed anti-depressants are handed to people who are not initially diagnosed with depression. The demand among males is deemed the highest, according to the study, with around 76,29% of the cases corroborating, especially between the ages of 40 and 60, with 40% being relegated to the remaining age groups. Conclusion: The statistics show that the amount of issued anti-depressant medication is still within the international norms, even less so than what would have foreseen in country going through similarly pressing hardships and crises; hitting about 7% released for the treatment of medical cases undiagnosed with medical depression, and 76,00% aimed at ones clinically diagnosed and warranting the prescription.